Optimization of the extraction process and metabonomics analysis of uric acid-reducing active substances from Gymnadenia R.Br. and its protective effect on hyperuricemia zebrafish - Chen, Tianrong; Pubu, Duoji; Zhang, Wenhui; Meng, Shengya; Yu, Cuicui; Yin, Xiaoqing; Liu, Jiale; Zhang, Yuhong (Frontiers in Nutrition, 2022)
Abstract As Gymnadenia R.Br. (Gym) has an obvious uric acid-lowering effect, but its specific bioactive substances and mechanism are still unclear. To find out the key metabolites and metabolic pathways related to the reduction of uric acid (UA) by Gym. Firstly, based on the xanthine oxidase (XOD) inhibition model in vitro, the extraction process of urate-lowering active substances from Gym was optimized. Then, the Ultra-high-performance liquid chromatography and Q-Exactive mass spectrometry based on non-targeted metabolomics analysis of Traditional Chinese Medicine were performed on Gym with 95% (low extraction rate but high XOD inhibition rate) and 75% (high extraction rate but low XOD inhibition rate) ethanol concentration, respectively, for comparison. Finally, the protective effect of ethanolic extract of Gym on zebrafish with Hyperuricemia (referred to as HUA zebrafish) was explored. The results showed that when the ethanol concentration was 95%, the inhibition rate of Gym on XOD was 84.02%, and the extraction rate was 4.32%. Interestingly, we found that when the ethanol concentration was 75% and the other conditions were the same, the inhibition rate of Gym on XOD was 76.84%, and the extraction rate was 14.68%. A total of 539 metabolites were identified, comprising 13 classes, including 48 flavonoids, 57 polyphenols, 69 alkaloids, 129 terpenoids, 3 quinones, 36 phenylpropanoid, 24 organic acids, 16 amino acids, 13 sugar and alcohol, 42 lipids and aromatics, 12 coumarins and lignans, 11 carboxylic acid and organic oxygen, and 79 miscellaneous, etc. Among them, 162 different metabolites were screened, of which 123 were up-regulated and 39 were down-regulated. The ethanolic extract of Gym could significantly reduce the contents of UA, BUN, CRE, ROS, MDA, and XOD activity in HUA zebrafish and acutely reduce the activity of SOD, which might be related to its antioxidant protection and reduce the oxidative stress response. Along with the flavonoids, polyphenols, alkaloids, terpenoids, and phenylpropanoids, the ethanolic extract of Gym may be related to the UA-lowering effect of Gym.